A semi analytical iterative method for solving the emden-fowler equations / Mat Salim Selamat ... [et al.] - Selamat, Mat Salim; Tokachil, Mohd Najir; Burhanddin, Noor Aqila; Murad, Ika Suzieana; Razali, Nur Farhana (2021)
Emden-Fowler equations are frequently encountered in physical and natural sciences. However, the Emden-Fowler solution is complicated due to singularity behaviour at the origin. Emden-Fowler equations are solved in this paper using a semi analytical iterative method (SAIM) that combines analytical and numerical computation. This method provides an exact solution to the Emden-Fowler equations, and transformation approaches are implemented to overcome the difficulties associated with singularity behaviour. As a result, the exact solutions of Emden-Fowler equations are successfully obtained using the SAIM. This shows that the SAIM is very effective and reliable, and that no restrictive assumptions for nonlinear terms are required. Furthermore, comparisons with the exact solutions and the solutions obtained by the variational iterative method (VIM) show the efficiency of SAIM in solving equations with singularity.